The effects of TiO2 nanoparticles and polydopamine on the structure, separation, and antifouling properties of PPSU membrane. Issue 11 (24th July 2022) - Pakizeh, Majid; Azinfar, Ferial; Safarnia, Mehrnaz; Raji, Foad
ABSTRACT: One of the most efficient and cost-effective technologies for removing dye pollutants from industrial effluents is membrane separation. This study aims to investigate the effect of modified nanocomposite polyphenylsulfone (PPSU) membrane for removing Direct Orange102 (DO) dye from aqueous solutions. For this purpose, the PPSU membrane was surface modified by polydopamine (PPSU/PD) to improve its hydrophilic properties and separation performance. Then, a nanocomposite membrane, PPSU/PD/TiO2, was prepared by coating the surface of PPSU/PD with different dosages of TiO2 nanoparticles. The prepared PPSU/PD and PPSU/PD/TiO2 samples were characterized by employing attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), and contact angle measurements. The ATR-FTIR analysis and FESEM images indicated that polydopamine and TiO2 were successfully coated on the surface of the membranes. Also, the results showed an increment in the hydrophilicity and roughness of the membrane after the addition of TiO2 nanoparticles. The performances of the fabricated membranes were compared in the separation of DO dye, Na2 SO4, and bovine serum albumin (BSA). The best flux and rejection were obtained at 2 mg/ml of dopamine and 0.03 wt% of TiO2 loading. The prepared PPSU/PD/TiO2 membrane with high water flux provided impressive salt and dye removal. The results revealed that dye rejection increased from 80.5% for the PPSU membrane to 90% for the PPSU/PD membrane with a flux of 36 Lm −2 h −1 . For the PPSU/PD/TiO2 membrane, dye rejection and flux improved to 96.8% and 82 Lm −2 h −1, respectively. The incorporation of TiO2 nanoparticles and polydopamine on the PPSU membrane surface enhanced the flux recovery ratio (FRR%) from 60.2% to 87%. The results of this study confirmed that modification of PPSU membrane by polydopamine and TiO2 nanoparticles leads to the improvement of the antifouling behavior and separation performance of the fabricated membrane toward the DO dye removal from aqueous solutions. ABSTRACT: uf0001